2006
DOI: 10.1177/1078087406290116
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Impact of Terrorist Incidents on the Italian Hospitality Industry

Abstract: Acts of terror are intended to incite fear and intimidation, which makes tourism particularly susceptible to attacks. Because the hospitality industry serves as a useful barometer of the indirect impact of attacks, we examine the impact of terrorist incidents on lodging-use rates in Italy between 1995 and 1997. We make use of data on domestic as well as international terrorism at the city level to explore more localized implications of terrorist incidents. We find that lodgings used by foreign visitors are the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 22 publications
(24 reference statements)
1
23
0
1
Order By: Relevance
“…However, there is limited evidence that a differentiated impact with respect to international visitors may exist. For example, Greenbaum and Hultquist (2006) found that demand for lodgings used primarily by domestic visitors to Italy is less sensitive to terrorist attacks. In the US, traces of a substitution effect between 'safe' domestic destinations (i.e.…”
Section: The Impact Of Terrorism On Tourismmentioning
confidence: 98%
“…However, there is limited evidence that a differentiated impact with respect to international visitors may exist. For example, Greenbaum and Hultquist (2006) found that demand for lodgings used primarily by domestic visitors to Italy is less sensitive to terrorist attacks. In the US, traces of a substitution effect between 'safe' domestic destinations (i.e.…”
Section: The Impact Of Terrorism On Tourismmentioning
confidence: 98%
“…The topic of terrorism spillover effects has produced a considerable amount of literature (Veréb, Nobre, & Farhangmehr, 2018). The decline in tourists' arrivals and receipts caused by terrorism is well documented in several countries and regions since the 90s and has affected countries like Spain (Enders & Sandler, 1991), European countries ( (Enders, Sandler, & Parise, 1992;Radić, Dragičević, & Sotošek, 2018), the Mediterranean region (Drakos & Kutan, 2003), non-democratic countries and Africa (Blomberg, Hess, & Orphanides, 2004), the USA (Bonham, Edmonds, & Mak, 2006;Goodrich, 2002), Israel (Eckstein & Tsiddon, 2004;Fleisher & Buccola, 2002;Morag, 2006;Pizam & Fleischer, 2002), Italy (Greenbaum & Hultquist, 2006), Nepal (Baral, Baral, & Nigel, 2004), Ireland (O'Connor, Stafford, & Gallagher, 2008), Fiji and Kenya (Fletcher & Morakabati, 2008), Nigeria (Adora, 2010); Turkey (Feridun, 2011;Ozsoy & Sahin, 2006), Pakistan (Raza & Jawaid, 2013), the Middle East (Bassil, 2014), the Caribbean (Lutz & Lutz, 2018), Tunisia (Lanouar & Goaied, 2019), and worlwide (Liu & Pratt, 2017;Llorca-Vivero, 2008;Neumayer & Plümper, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding economic effects is especially of interest in countries where tourism is an important source of revenue, and which are also attacked, such as Greece, Spain, Turkey, and Kenya. Research on tourism in one country (Buigit & Amendah, ; Greenbaum & Hultquist, ; O'Connor, Stafford, & Gallagher, ) or a small number of countries (Drakos & Kutan, ; Enders & Sandler, ) has identified some key effects, but these studies usually do not offer greater comparability across industries or contexts. In their study of the effect of terrorism on Kenyan tourism, Buigit and Amendah () estimated the losses associated with a one‐unit rise in fatalities to be more than 2,500 visitors and close to 160 million shillings annually.…”
Section: Considerationsmentioning
confidence: 99%
“…Investigating many subnational spatial units, for as long a period as possible, can help identify the underlying and “before” characteristics of a community which supports greater or less resilience. For example, Greenbaum and Hultquist () uncovered interesting effects of terrorism specifically on local lodging‐use rates in Italy, but their study was limited to the period 1995–1999, not accounting for other possible interactions in the external environment, e.g., demand trends. Gaibulloev and Sandler () studied 51 African countries over a long period (1970–2007) and identified new regional effects of transnational terrorism on income per capita growth.…”
Section: Prioritiesmentioning
confidence: 99%